Hydrophobic Silica-Aerogel Integrated Polyacrylonitrile Nanofibers - ARAT, REFİK; Baskan, Havva; Ozcan, Gülay; Altay, Pelin (Sage Publications Inc., 2020)
Owing to its high specific surface area, high thermal stability and excellent thermal insulation, silica aerogel is used as an insulating material in protective clothing. In this study, the hydrophobicity and thermal insulation properties of the electrospun polyacrylonitrile (PAN) nanofibers were enhanced by integrating silica aerogel (SA), which was synthesized using silicic acid as silica precursor instead of silicon alkoxides or sodium silicate and modified with phenyltrimethoxysilane. The electrospun PAN-SA composite nanofibers showed higher surface roughness and hydrophobicity (water contact angle of 142 degrees) compared to the smooth and hydrophilic PAN (control) nanofiber. Further, the thermal stability of the PAN nanofibers was increased by 17 degrees C while their thermal conductivity was decreased from 15.8 W/mK to 0.4 W/mK (reduction of 97.5%). These features make the PAN-SA composite nanofibers particularly suitable for use in thermal insulation protective clothing.
Keywords: Silica Aerogel; Pan Nanofiber; Composite; Thermal Properties; Protective Clothing